THELODONT SCALES FROM THE LOWER DEVONIAN RED BAY GROUP, SPITSBERGEN - Blom H.; Goujet D. (My University, 2002)
Scales of nine thelodont taxa are described from the Red Bay Group of Spitsbergen, also characterized by its assemblage of other typical Early Devonian vertebrates. The four thelodont-bearing horizons of the lower Fraenkelryggen Formation yield typical Lochkovian thelodont assemblages, containing Boreania minima, Canonia grossi, Nikolivia depressa sp. nov., Nikolivia elongata, Nikolivia gutta and Turinia pagei. One horizon from the younger Ben Nevis Formation has a similar thelodont assemblage, except for two new taxa; Apalolepis angelica sp. nov. and Turinia barentsia sp. nov. The appearance of Turinia polita and the disappearance of Boreania minima is also characteristic for this assemblage. Comparison with similar faunas from the Northern Hemisphere supports this faunal change and allows further elaboration of Early Devonian thelodont biostratigraphy.
Keywords: THELODONT SCALES; LOWER DEVONIAN; SPITSBERGEN; RED BAY GROUP; SYSTEMATICS; CORRELATION; BIOSTRATIGRAPHY; Devonian; Lochkovian; Paleozoic::Devonian; Paleozoic::Devonian::Lower::Lochkovian; Палеозой::Девонская; Палеозой::Девонская::Нижний::Лохковский